2011
DOI: 10.1021/ie202111k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alkylimidazoles as Physical Solvents for CO2/CH4 Separation

Abstract: 1-n-Alkylimidazoles are a class of tunable solvents with low volatility and low viscosities. Although imidazoles have been known for some time in the pharmaceutical industry, and as convenient precursors for synthesizing imidazolium-based ionic liquids (ILs), only recently have they been given consideration in some of the same solvent-based separations applications that ILs have been studied for, such as post-combustion CO 2 capture and natural gas treating. "Sweetening", the removal of CO 2 , H 2 S, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 44 publications
6
76
0
Order By: Relevance
“…The CH 4 solubility decreases 15% on average from 303 to 323 K, while the value is 30% for the CO 2 solubility at the same temperature range. Similar observation has also been mentioned in the literature (Shannon et al, 2011(Shannon et al, , 2013.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The CH 4 solubility decreases 15% on average from 303 to 323 K, while the value is 30% for the CO 2 solubility at the same temperature range. Similar observation has also been mentioned in the literature (Shannon et al, 2011(Shannon et al, , 2013.…”
Section: Resultssupporting
confidence: 91%
“…It has been reported that the CO 2 solubility is much higher than the CH 4 solubility in ILs [bmim][Tf 2 N] and [bmim] [BF 4 ] (Mortazavi-Manesh et al, 2013;Raeissi and Peters, 2010). Therefore, ILs exhibit a high CO 2 /CH 4 selectivity which can compete with the most commercial physical solvents (Althuluth et al, 2012;Anthony et al, 2002;Karadas et al, 2010) approach to make ILs applicable in the CO 2 /CH 4 separation system is to blend ILs with other commercially available solvents (Shannon et al, 2011). These mixtures can retain the desired properties of ILs but keep the viscosity relatively low as well as reduce the overall solvent costs.…”
Section: Introductionmentioning
confidence: 99%
“…ILs have emerged as a new class of physical solvents. They combine different interesting properties: they exhibit the lowest vapor pressures of any physical solvents, they can be easily introduced in various amounts in a wide variety of polymers and they display high thermal stability . Moreover some of them, such as imidazolium‐based ILs have been at the forefront of research into new solvents for gas processing …”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that a solution containing both an alkylimidazole and an amine could exceed the conventional 1:2 (CO 2 :amine) stoichiometry as the alkylimidazole could serve as a H + acceptor, and increase the overall CO 2 capacity per volume of solvent. [30] A concern for all amine-based solvents in post-combustion CO 2 capture from coal-fired power plants is their degradation by flue gas components, especially SO 2 . [22] Yet for imidazole-amine solutions, we observed that viscosity was not negatively impacted in a significant manner when the imidazole was present and that anhydrous viscosities of < 40 cP at ambient temperature were observed for CO 2 -rich samples, which could be even further reduced upon introduction of water or via choice of imidazole.…”
Section: Experimental and Computational Resultsmentioning
confidence: 99%